2012
DOI: 10.1007/s00167-012-2264-3
|View full text |Cite
|
Sign up to set email alerts
|

Knee joint infection after ACL reconstruction: prevalence, management and functional outcomes

Abstract: The prevalence of septic arthritis after an ACL reconstruction in this series was 1.8 %. Arthroscopic lavages along with antibiotic treatment led us to preserve all but one graft. Functional outcomes in the infected patients were not as good as those obtained in patients without infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 30 publications
4
100
1
4
Order By: Relevance
“…Elevated acute phase reactants, determination of bacteria in the gram stain of the sample taken from the joint, or increased levels of polymorphonuclear leukocytes may help the diagnosis. The culture of the sample obtained from the joint fluid by puncture is necessary to identify the pathogen in the diagnosis of septic arthritis and to determine which antibiotics to administer [1,19]. The absence of bacterial proliferation in the sample obtained from the joint fluid does not exclude a diagnosis of septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated acute phase reactants, determination of bacteria in the gram stain of the sample taken from the joint, or increased levels of polymorphonuclear leukocytes may help the diagnosis. The culture of the sample obtained from the joint fluid by puncture is necessary to identify the pathogen in the diagnosis of septic arthritis and to determine which antibiotics to administer [1,19]. The absence of bacterial proliferation in the sample obtained from the joint fluid does not exclude a diagnosis of septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest rate was presented by Indelli et al [2], who reported a rate of 0.14 % for septic arthritis in a series of 3500 consecutive ACLR patients. On the other hand, the highest published rates are by Torres-Claramunt et al [3] (1.8 % in a series with 810 consecutive ACLR) and Shollin-Borg et al [4] (1.7 % in a series with 575 ACLR). Viola et al [5] reported a retrospective series with 13 patients diagnosed with septic arthritis following ACLR performed with a bone-patellar tendonbone (BPTB) autograft.…”
Section: Prevalencementioning
confidence: 93%
“…aureus and CNS (S. epidermidis and other coagulasenegative species) are the most common bacteria found in most series [2,3,5,7,10,11,[14][15][16]. Additionally, different methicillin-resistant S. aureus or anaerobium microorganisms have also been cultured as the origin of such infections.…”
Section: Aetiopathologymentioning
confidence: 99%
See 2 more Smart Citations